Eustachian tube dysfunction in children with cleft palate: A tympanometric time‐to‐event analysis. (13th June 2019) - Funamura, Jamie L.; Said, Mena; Lin, Sharon J.; McKinney, Samantha; Tollefson, Travis T.
Abstract : Objectives: To characterize the duration of Eustachian tube dysfunction in children with cleft palate compared to those without cleft palate by performing time‐to‐event analysis on tympanometric data. To determine predictive characteristics of earlier achievement of normal tympanograms in children with cleft palate. Methods: Longitudinal tympanometric data from a minimum of 10 years at a single center were reviewed for children with cleft palate born in the years 2003 through 2007. Children with cleft lip without cleft palate born in the same years were used as a reference group to compare children with similar length of follow‐up. The association between time to sustained normal (type A) tympanograms with patient demographics, clinical characteristics, and otologic history was evaluated using time‐to‐event analysis and compared with log rank tests. Adjusted and unadjusted hazard ratios were estimated using Cox proportional hazard models. Results: The median age of achieving a type A tympanogram in children with cleft palate was 9.9 years for one and 12.1 years for both ears, compared to 7.1 and 7.4 years in children with cleft lip only ( P < 0.0001). On multivariate analysis, clinical characteristics such as the severity of palatal clefting or the presence of a cleft‐associated syndrome/sequence were not predictors of a longer time to a type A tympanogram. Conclusion: Our results help characterize the observation that there is delayed time to normal Eustachian tube function in children with cleft palate, which is not associated with the degree of palatal clefting. Level of Evidence: 3b Laryngoscope, 130:1044–1050, 2020